The Influence of a Meritocracy System on the Quality of Public Services - Qomar, Maslia; Ahkam, Syuaib (STMIK Widya Cipta Dharma, 2025)
This study examines the relationship between the merit system and the quality of public services, with the work motivation of state civil apparatus (ASN) as a mediator, using a case study in the West Sumbawa Regency Government. The background of the study is based on the need to strengthen bureaucratic professionalism through recruitment, promotion, competency development, and talent management practices based on qualifications and performance, amidst implementation challenges at the regional level influenced by limited capacity and a patronage culture. The research aims to build an empirical understanding of the extent to which the merit system affects the quality of public services, both directly and indirectly, through increased work motivation. This study uses a quantitative cross-sectional approach with a Likert scale-based instrument to measure the dimensions of meritocracy, work motivation, and public service quality adapted from the SERVQUAL model. Data analysis was performed using Partial Least Squares-Structural Equation Modeling (PLS-SEM), testing construct validity and reliability, as well as the significance of direct and indirect paths. The findings show that all merit components—from recruitment to talent management—significantly influence the formation of a strong merit system, with the greatest impact coming from competency development and talent management. The established merit system contributes positively to public service quality, reflected in the dimensions of reliability, responsiveness, assurance, empathy, and tangibles, with work motivation proven to partially mediate this relationship. These results affirm the importance of integrating merit-based HRM policies with strategies to strengthen ASN motivation as a continuous effort to improve service quality and public trust.